Kombinasi Sinar Inframerah, Cadexomer Iodine Powder, dan Zinc Cream Pada Diabetic Foot Ulcer (DFU): Sebuah Case Report - Rustianti; Nursiswati, Nursiswati; Kurniawan, Titis; Setiawan, Cencen Hendra (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2024)
The management of Diabetic Foot Ulcer (DFU) infections has undergone many developments. Some of therapies used, namely infrared, cadexomer iodine, and zinc cream as single therapies that have been proven effective. However, the combinations of these therapy is not yet known whether it’s more effective or not than single or double therapy. It’s important to know the outcome of combination of these therapys on the wound healing process. This case report was applied to DM Type 2 patient with DFU score 47 from Bates-Jansen Wound Assessment Tool (BJWAT) and hyperglycemic condition (355 mg/dL). Wound treatment was carried out using the TIME Concept and applying 3M principles which were repeated in 4 home visits for 11 days. The result showed wound improvement as indicated by decrease in BJWAT score from 47 to 38. The improvement in this case was supported by the strength of each therapy which is combined in the wound healing process compared to single or double therapy. The client's wound care has the potential to address bacterial colonization and prevent biofilm formation, maintain wound moisture, and autolysis of necrotic tissue in a faster time. However, there are several complicating factors of client’s wound healing process, namely hyperglycemia, non-adherence of insulin injection, infection, hypertension, and hyperurisemia. The combination of these three therapies was shown to wound healing in terms of wound depth, type and amount of necrotic tissue, peripheral edema, granulation, and epithelialization and accelerate wound repair compared to single or double combinations.